Implementasi Pemisahan Kelas (Segregasi Gender) Peserta Didik dan Implikasinya Terhadap Motivasi Belajar di MTS N 4 Pasaman Barat - Ismy Azizah; Puti Andam Dewi; Arridha Helty (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2023)
Judicial practice shows a tendency for plaintiffs to also attract DJKI as a Co-Defendant in lawsuits to nullify registered trademarks. In this regard, there are considerations from the Judge in Supreme Court Decision No. 457 K/Pdt.Sus-HKI/2022, which states that DJKI must be withdrawn as a Co-Defendant. This research aims to determine whether the judge's considerations in the decision are in accordance with Law Number 20 of 2016 concerning Trademarks and Geographical Indications, as well as to examine the position of the DJKI after the decision. The research method in this legal research is based on a juridical-normative approach. The research results show three conclusions that can be drawn—first, Supreme Court Decision no. 457 K/Pdt.Sus-HKI/2022 is not in line with Law Number 20 of 2016 concerning Trademarks and Geographical Indications, the opinion of intellectual property law experts, the theory of government officials' compliance with court decisions, and the views of judges in 11 (eleven) court decisions have the same permanent legal force—Second, the plaintiff's "Yunteng" mark qualifies as a well-known mark, and there are substantial similarities between the Plaintiff's and the Defendant's trademark—Third, even though the decision deviates from what ought to be, the decision is a Supreme Court Decision that has the potential to be used as a reference for subsequent judges in similar cases.